PENGARUH MULTIMEDIA INTERAKTIF POWTOON TERHADAP KEMAMPUAN BERFIKIR KREATIF SISWA PADA MATERI BANGUN RUANG KELAS V SDN 02 MUARA CIUJUNG TIMUR RANGKASBITUNG - Fajar, Muhamad; Hanif, Muhammad; Fitriasari, Novi Sofia (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The essence of education is a process in an effort to build people who can know themselves and explore their potential, whether from a local, national, or global scope though. One of the subjects in elementary school teaching is mathematics which is one of the studies that is always interesting to discuss because of differences in characteristics, especially between the nature of children and the nature of mathematics. For this reason, it is necessary to have a bridge that can neutralize these differences or conflicts. This research was conducted to determine the effect of Powtoon interactive multimedia on students' creative thinking ability in Solid Figure material. This study used interactive multimedia in the form of a video from the Powtoon application along with 10 essay questions. This research is a Quasi-Experimental Design in the form of a Non-Equivalent Control Group Design. The number of samples taken consisted of class V A totaling 36 students as the experimental class and class V B, totaling 36 students as the control class. The data analysis technique consisted of prerequisite tests including normality test, homogeneity test, and independent sample t-test. The results of the data from the Independent Sample T-test on the pre-test and post-test data are the sig. (2-tailed) of 0.000 0.05. Hence, it can be concluded that there are differences in the creative thinking abilities of mathematics students between the experimental class using interactive multimedia Powtoon and the control class using only conventional methods, namely power point in class V Public Elementary School 02 Muara Ciujung Timur Rangkasbitung.